The present simple form in the written work of Bangladeshi EFL learners - Kayum, Muhammad Afsar; Mohammad Lotfie, Maskanah (2020)
In the EFL context of Bangladesh, tense is a significant and complex part of learners’ written work. The preliminary assumptions of the causes of learners’ confusions and complexity in acquiring the grammatical patterns of tense might be the cross-linguistic influence (CLI) which is quite synonymous with the terms ‘language transfer’ and ‘L1 interference’ that all suggest the influence of one language upon another; or more specifically the influence of native language in the process of second or foreign language acquisition. This influence may be a ‘positive transfer’ that refers to the facilitating effects of one language in acquiring another; or a ‘negative transfer’ i.e. the divergences due to some differences between the target language and the native one of the learners (Odlin, 2013). The objective of this paper is to present a study that investigates the plausible causes of the similarities and differences of the features of present simple form in the written work of Bangladeshi EFL learners and in British Standard English. In doing so, systematic and thorough content analysis is employed on the data of written composition on a specific topic, collated from 200 postgraduate advance level Bangladeshi EFL learners. The study attempts to contribute to the theoretical development of the cross-linguistic study in the written English in Bangladesh basing on the present CLI and second language acquisition theories.